New Syntheses of 3-Aroylflavone Derivatives; Knoevenagel Condensation and Oxidation versus One-Pot Synthesis - Vaz, Patrícia A. A. M.; Pinto, Diana C. G. A.; Rocha, Djenisa H. A.; Silva, Artur M. S.; Cavaleiro, José A. S. (Synlett, 2012)
Two syntheses of 3-aroylflavones have been established. In the first synthesis the use of microwave irradiation led to an improvement in the yields of both the Knoevenagel condensation of β-diketones with aldehydes to afford 3-aroylflavanones and of their oxidation to 3-aroylflavones. In the second and more general synthesis, a novel and efficient procedure for 3-aroylflavones involves a one-pot reaction between 2′-hydroxyacetophenones and aroyl chlorides in the presence of lithium bis(trimethylsilyl)amide.
Keywords: Claisen condensation; Knoevenagel condensation; lithium bis(trimethylsilyl)amide; microwaves